Novel high resolution melt curve assay for the analysis of predominance of Helicobacter pylori clarithromycin resistance. Issue 4 (2nd August 2019) - Boltin, Doron; Ashorov, Olga; Benejat, Lucie; Hamouda, Dalal; Belfer, Rachel Gingold; Niv, Yaron; Dickman, Ram; Perets, Tsachi Tsadok
ABSTRACT: Clarithromycin resistance is the most common cause of Helicobacter pylori treatment failure and it is attributed to three point mutations, A2142G, A2142C and A2143G, within the 23S rRNA gene. We aimed to determine the prevalence of H. pylori clarithromycin resistance using a novel high resolution melt assay. A total of 151 stool samples were collected from treatment-naïve patients with general gastric discomfort who also performed 13 CO2 breath tests. Stool antigen tests were also performed on 126 of the 151 stool samples collected. Bacterial DNA was extracted from the stool and analyzed by comparing it with four reference plasmids incorporating the three mutations and the wild type (WT) sequences. The melt assay detected 106 H. pylori positive samples, of which 54 had a WT sequence, and 52 had a point mutation associated with clarithromycin resistance, including A2142G in 10, A2142C in 13, A2143G in 18 and heterozygosity (multiple peaks) in 11. Compared with the gold standards ( 13 CO2 breath and stool antigen tests), the melt assay had a sensitivity of 100% and 99% and a specificity of 82% and 78%, respectively. Therefore, our stool-based molecular assay is able to identify H. pylori infection and clarithromycin resistance. It could be used for screening prior to administration of clarithromycin eradication therapy. Abstract : Our stool-based high resolution melt assay is an accurate and non-invasive tool for the diagnosis of Helicobacter pylori infection and clarithromycin resistance.